2008
DOI: 10.1088/1674-1056/17/12/038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of D α (H α ) spectrum emitted in front of the limiter in HT-7

Abstract: In order to understand the recycling and emission processes of hydrogen atoms in HT-7, spectral profiles of the Dα(Hα) line emitted in front of the limiter have been observed with a high-resolution spectrometer and simulated by using the neutral particle transport code DEGAS 2. The results show that four processes are necessary to interpret the Dα(Hα) line shape: 1) atom desorption, 2) molecular dissociation, 3) particle reflection, and 4) charge-exchange. The products of the first two processes are cold atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In particular, the mechanisms for the dissociation of molecules into atomic species within the plasma edge need to be both qualitatively and quantitatively understood. These processes are likely responsible for the large number of slow hydrogen atoms with kinetic energies less than 0.5 eV detected in the plasma edge layer of tokamaks (Mertens et al 2001, Huang et al 2008. A recent investigation by Hollmann et al (2006) in the DIII-D plasma edge has revealed highly excited D 2 , with an X 1 + g rotational temperature up to 10 000 K and vibrational temperature up to 30 000 K. Their analysis has also shown that collisonal excitation and ionization of D 2 and the dissociative recombination of D + 2 with electrons are major mechanisms for the production of D atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the mechanisms for the dissociation of molecules into atomic species within the plasma edge need to be both qualitatively and quantitatively understood. These processes are likely responsible for the large number of slow hydrogen atoms with kinetic energies less than 0.5 eV detected in the plasma edge layer of tokamaks (Mertens et al 2001, Huang et al 2008. A recent investigation by Hollmann et al (2006) in the DIII-D plasma edge has revealed highly excited D 2 , with an X 1 + g rotational temperature up to 10 000 K and vibrational temperature up to 30 000 K. Their analysis has also shown that collisonal excitation and ionization of D 2 and the dissociative recombination of D + 2 with electrons are major mechanisms for the production of D atoms.…”
Section: Introductionmentioning
confidence: 99%